2016
DOI: 10.1002/ajim.22668
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in a combined cohort of uranium enrichment workers

Abstract: Objective To examine the patterns of cause-specific mortality and relationship between internal exposure to uranium and specific causes in a pooled cohort of 29,303 workers employed at three former uranium enrichment facilities in the United States with follow-up through 2011. Methods Cause-specific standardized mortality ratios (SMRs) for the full cohort were calculated with the U.S. population as referent. Internal comparison of the dose-response relation between selected outcomes and estimated organ doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
(53 reference statements)
1
28
0
Order By: Relevance
“…Most of latter studies reported ERR of 10% per gray. Nevertheless, it should be noted that several previous α-radiation low-dose radiation studies obtained similarly elevated risk estimates in the analyses of lung cancer mortality and internal lung dose due to uranium: French uranium miners (ERR/Gy 503.2, 95% CI 121.5 to 1225.0),41 US Fernald Feed Materials Production Centre (ERR/Gy 22, 95% CI −9.3 to 70)42 and US uranium enrichment workers (ERR/Gy −750, 95% CI −2310 to 1120) 43. These high estimates may indicate a difficulty in extrapolating risk above the doses concentrated in a very low dose range and prove a necessity for future combined studies to gain in statistical power.…”
Section: Discussionmentioning
confidence: 85%
“…Most of latter studies reported ERR of 10% per gray. Nevertheless, it should be noted that several previous α-radiation low-dose radiation studies obtained similarly elevated risk estimates in the analyses of lung cancer mortality and internal lung dose due to uranium: French uranium miners (ERR/Gy 503.2, 95% CI 121.5 to 1225.0),41 US Fernald Feed Materials Production Centre (ERR/Gy 22, 95% CI −9.3 to 70)42 and US uranium enrichment workers (ERR/Gy −750, 95% CI −2310 to 1120) 43. These high estimates may indicate a difficulty in extrapolating risk above the doses concentrated in a very low dose range and prove a necessity for future combined studies to gain in statistical power.…”
Section: Discussionmentioning
confidence: 85%
“…The details on the cohort and case ascertainment were described previously . Briefly, the study subjects included a pooled cohort of workers from three uranium enrichment facilities: K‐25, PORTS, and PGDP.…”
Section: Methodsmentioning
confidence: 99%
“…Operations at fuel cycle facilities present a potential for worker exposures to various uranium compounds that are known or suspected to cause adverse human health effects. Yiin et al examined the patterns of cause‐specific mortality in a combined cohort of 29 303 workers from three gaseous diffusion plants (GDP) in the United States: the Oak Ridge Gaseous Diffusion Plant (also known as K‐25) in Oak Ridge, Tennessee (TN), the Portsmouth Gaseous Diffusion Plant (PORTS) in Piketon, Ohio (OH), and the Paducah Gaseous Diffusion Plant (PGDP) in Paducah, Kentucky (KY). Although workers at these former uranium enrichment facilities had significantly lower standardized mortality ratios (SMRs) for most diseases than the U.S. population, excess SMRs that were not statistically significant were observed in kidney cancer, bone cancer, non‐Hodgkin's lymphoma (NHL), and chronic renal diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Recently, several epidemiological studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14] were dedicated to identifying potential health effects from incorporated radionuclides. To do so, the exposure and/or dose of individuals were quantified and associations with health status investigated.
…”
mentioning
confidence: 99%